Parental demographics and preschool childrens theory of mind - Farhadian, Mokhtar; Abdullah, Rohani; Mansor, Mariani; Redzuan, Maarof; Kumar, Vijay (Kamla-Raj Enterprises, 2010)
This research investigates the difference between theory of mind (ToM) and parental demographics of preschool children. One hundred and sixty six 3.6- to- 5.6 year old children were tested on three standard false belief tasks and a verbal ability test. A significant difference was found between mother’s occupational status and ToM. However, hierarchical regression analysis showed that mother’s occupational status was a significant predictor of children’s ToM development after controlling for age and verbal ability.